Hyperintense Putaminal Rim Sign Is Not a Hallmark of Multiple System Atrophy at 3T - Lee, Wei-Hsing (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Hyperintense putaminal rim (HPR) on the T2-weighted imaging, which has been observed in our daily practice while reading 3T brain images, has been described as a finding typical of multiple system atrophy (MSA). We hypothesized that the HPR sign is not an exclusive hallmark of MSA at a high magnetic field strength, but rather may be a normal finding. METHODS: Ten consecutive clinically healthy age-matched adults who showed recognizable HPR at 3T were subsequently examined on a 1.5T imaging system within 2 hours. MR examination included axial T2-weighted fast spin-echo (FSE), fluid attenuated inversion recovery (FLAIR) on a 3T scanner, and equivalent T2-weighted FSE at 1.5T. MR images were obtained parallel to the intercommissural plane. All the images were interpreted by 2 experienced neuroradiologists. RESULTS: All 10 subjects (3 men and 7 women; aged 52 ± 6.1 years [range, 44–61 years], expressed as mean ± SD) with the positive HPR sign on axial T2-weighted FSE at 3T had negative findings at 1.5T. Such hyperintense rim was also vague or absent on the 3T-FLAIR images. CONCLUSION: Our data suggest that the HPR at 3T scans is a nonspecific, normal finding. FLAIR may be helpful in discriminating between normal subjects and patients with MSA in case of isolated HPR at 3T.